Ayudenme por fa, con resolucionn!
Adjuntos:
![](https://es-static.z-dn.net/files/d01/1fa0858b0f8661902391c36c428006b8.jpg)
Respuestas a la pregunta
Contestado por
1
Respuesta:
1
Explicación paso a paso:
*se sabe:
➧ a³-b³=(a-b)(a²+b²+ab)
➧ a²-b²=(a-b)(a+b)
➧ (a+b)²=a²+b²+2ab
*desarrollando:
(a+b)²+1=(a+1)(b+1)
a²+b²+2ab+1=ab+a+b+1
a²+b²+2ab=ab+a+b
a²+b²+ab=a+b
[(a³-b³)/(a-b)]= a+b
a³-b³=(a-b)(a+b)
a³-b³=a²-b²
a³-a²=b³-b²
*piden:
E=(a³-a²)/(b³-b²)
E=(b³-b²)/(b³-b²)
E=1
mayki58otkfry:
Graciass enserio:;)
Otras preguntas
Informática,
hace 6 meses
Matemáticas,
hace 6 meses
Biología,
hace 1 año
Ciencias Sociales,
hace 1 año
Castellano,
hace 1 año
Física,
hace 1 año